Research progress on the mechanism of action of Salvia miltiorrhiza and its components in the treatment of endometrial carcinoma: Mechanism of action of S. miltiorrhiza in EC - Zhang, Chunhua; Liu, Qing; Qi, Ziyi; Chen, Weiping; Zeng, Li (Cellular and Molecular Biology, 2024)
The incidence and mortality of endometrial carcinoma (EC) are increasing year by year. Although the curative effect of surgery and commonly used drugs is clear, it is accompanied by obvious side effects, and safe and effective means are urgently needed to promote the curative effect and decrease the toxicity of drugs. Traditional Chinese medicine has been passed down for thousands of years in China and has proved to be advantageous in the treatment of various cancers and the auxiliary enhancement and reduction of toxicity. This paper reviewed the role and internal mechanism of Salvia miltiorrhiza in preventing and treating endometrial carcinoma by referring to relevant literature and works, so as to more comprehensively understand and grasp the research status, effective components, curative effect and effective mechanism of S. miltiorrhiza in preventing and treating endometrial carcinoma, and provide ideas and basis for clinical use and basic research.